Following the last Neanderthals: Mammal tracks in Late Pleistocene coastal dunes of Gibraltar (S Iberian Peninsula). (1st August 2019) - Muñiz, Fernando; Cáceres, Luis M.; Rodríguez-Vidal, Joaquín; Neto de Carvalho, Carlos; Belo, João; Finlayson, Clive; Finlayson, Geraldine; Finlayson, Stewart; Izquierdo, Tatiana; Abad, Manuel; Jiménez-Espejo, Francisco J.; Sugisaki, Saiko; et al.
Abstract: The aeolian Pleistocene deposits recorded in the Rock of Gibraltar (S Iberian Peninsula) present a significant sedimentary thickness that fills the wide sea caves and covers its steep slopes. In Catalan Bay these deposits register the development of cliff-foot and rampant dunes that form a 35° sand ramp, 1 km long and up to 300 m in height formed by moderately to well-sorted sands, slightly carbonated and weakly cemented. This morphosedimentary evidence is associated with MIS 5−2 sea level fluctuations. Its internal structure shows lamination sets of 2–3 m in thickness and planar and trough cross-bedding. In these beds, five morphotypes of mammalian footprints have been recognized in vertical cross sections and convex hyporeliefs. Most of them present a moderate degree of conservation due to the poor cementation of the sands. These icnites are related to the activity of terrestrial mammals, possibly belonging to Homininae, Proboscidea, Artiodactila and Carnivora. The affinity between the footprints and their tracemakers has been established in the basis of their physical parameters, the shape of the footprints, their comparison with similar footprints and the correlation with the fossil fauna of vertebrates described for the Late Pleistocene in Gibraltar. These findings represent the first palaeoichnological record in the aeolian sediments of Gibraltar and indirectly corroborate the occupation of the coastal dune landscape by several terrestrial mammals during the Late Pleistocene. In addition, they help reconstructing the animal behaviour and interaction with the extensive dune systems that developed at the foot of the Rock slopes. The age of the tracks has been established within the MIS 2, during the probable Middle-Upper Palaeolithic transition in the climate refuge of Gibraltar. Highlights: The Late Pleistocene aeolianites on Gibraltar contain abundant mammal tracks. These deposits form a lower set of cliff-foot dunes and another of rampant sands. The fossil tracks are concentrated in two units dated by OSL in 28 ± 3 ka (MIS 2). The tracemakers identified are Homininae, Proboscidea, Artiodactila and Carnivora. A footprint is assigned to Homo neanderthalensis by a photogrammetric analysis.